Microfinance and Gender: Issues, Challenges and The Road Ahead. Issue 5 (4th May 2017) - Garikipati, Supriya; Johnson, Susan; Guérin, Isabelle; Szafarz, Ariane
Abstract: This special collection examines the claim that microfinance promotes gender equality. The focus is on three areas of the debate: first, the question of how successful microfinance has been in empowering women; second, whether and how negative gender discrimination operates within the sector; third, how power relations within and beyond the household shape the context and outcomes of microfinance initiatives. The papers in this collection demonstrate the divergence of circumstances and emphasise the need to go beyond the past searches for a simple narrative regarding the impact of microfinance. Rather, as the sector evolves and is incorporated into the mainstream financial system, the challenge ahead for researchers is to marshal the evidence on gendered dynamics to ensure that the gains made are built on through deeper understanding of why impact outcomes and processes differ and use this to inform new initiatives to further gender equality.